Knowledge, attitude and practice of MSD injuries from Malaysian employer perspective - Athirah, Nadia Nordin (UTM-NIOSH, 2016)
This study aims to assess the level of Knowledge, Attitude and Practices (KAP) on Musculoskeletal disorders (MSDs) from employer perspectives in Malaysia industries. A newly developed KAP questionnaire was distributed and answered by 45 employers. Most employers show good scores to the majority of items in Knowledge, Attitude and Practices sections. Pearson correlation is used in order to test the relationship between KAP scores and demographic profile and also KAP variables. It was found that knowledge has strong correlation r=0.291, p>0.05 with gender. The attitude component has a strong correlation (r=0.344, p>0.05) with age group. Whereas the practices component has good correlation with education level (r=0.249, p>0.05). However, the KAP variables show only knowledge and practices have a strong correlation(r=0.271, p>0.05).MSDs cases are increasing hence understanding the underlying KAP factors are crucial in order to tackle the problem.